8-week Aerobic Exercise and Vitamin D Supplementation: Impact on Hypertension With Vitamin D Deficiency - Mozaffar Janfaza; Mahsa Bahnamon; Roghaiyeh Afsargharehbagh (Research in Molecular Medicine)
Background: This research aims to investigate the performance of 8 weeks of aerobic exercise and vitamin D supplementation on nitric oxide (NO) and endothelin 1 (ET-1) indicators in patients with high blood pressure and vitamin D deficiency.